The Key Motivating Factors of Employee Retention : A Resource Based View - Akhtar, Tahir; Zahir, Ahmad; Tareq, Mohammad Ali; Mahdzir, Akbariah Mohd (Prabandhan: Indian Journal of Management, 2017)
The study explored how employees’ retention act as a valuable resource for corporate governance to increase and sustain firm’s performance. Phenomenological approach is used to collect information from a sample of 50 employees in the education sector. After conducting semi-structured interviews, six themes were developed by using various statements. The themes developed are the key motivating factors of employees’ retention that create awareness among the managers and the board members to help them in making different strategies of retaining employees and using them as a valuable resource to achieve sustainable organizational development.